IMPROVING HEALTH LITERACY UTILIZING THE HEALTH BELIEFS MODEL: PERCEIVED OBSTACLES IN HIV/AIDS PREVENTION VIA VIRTUAL REALITY APPLICATION AMONG ADOLESCENTS IN PANGKAJENE AND THE ISLANDS REGENCY - Rusli Taher1, Muh. Syafar*3, A. Indahwaty Sidin4, Stang5, Oedojo Soedirman6, Syamsiar S. Russeng7, Ridwan Amiruddin8 , Andi Armyn Nurdin9, Darwis10, Abdul Thalib11, (Chelonian Research Foundation, 2023)
Introduction: In an era marked by rapid change, enhancing health literacy among adolescents, particularly in the context of HIV/AIDS prevention, holds significant importance. The integration of virtual reality applications has the potential to alter adolescents' perceptions of risk and precautionary measures, catering to the needs of a generation increasingly immersed in technology during this digital age. Method: This study adopts a time-series non-equivalent control group design, with a substantial sample size of 44 individuals in both the intervention and control groups, totaling 88 participants. The sampling technique employed is consecutive sampling. The Health Literacy questionnaire for HIV/AIDS prevention incorporates a Virtual Reality-based Health Belief Model (HBM) approach. The study spans approximately 2 months, from June to August 2023. Results: The findings indicate a significant impact of the health literacy model utilizing virtual reality on perceived severity and susceptibility regarding HIV/AIDS among adolescents in Pangkajene Regency and Islands. Additionally, there is an observed increase in positive perceptions of the Health Belief Model, specifically in the perceived obstacles of HIV/AIDS prevention within the intervention group (VR), surpassing levels in the control group. Conclusions: This study underscores the positive influence of Health Literacy and virtual reality media in enhancing perceptions related to perceived obstacles in HIV/AIDS prevention among adolescents. Such insights carry substantial implications for modifying behaviors related to disease prevention. Keyword: Health Belief Model (HBM), Virtual Reality, HIV/AIDS, and adolescence